Clinical leadership development and education for nurses: prospects and opportunities - Joseph ML; Huber DL (Journal of Healthcare Leadership, 2015)
M Lindell Joseph, Diane L Huber College of Nursing, The University of Iowa, Iowa City, IA, USA Abstract: With the implementation of the Affordable Care Act, elevated roles for nurses of care coordinator, clinical nurse leader, and advanced practice registered nurse have come to the forefront. Because change occurs so fast, matching development and education to job requirements is a challenging forecasting endeavor. The purpose of this article is to envision clinical leadership development and education opportunities for three emerging roles. The adoption of a common framework for intentional leadership development is proposed for clinical leadership development across the continuum of care. Solutions of innovation and interdependency are framed as core concepts that serve as an opportunity to better inform clinical leadership development and education. Additionally, strategies are proposed to advance knowledge, skills, and abilities for crucial implementation of improvements and new solutions at the point of care. Keywords: clinical leadership, nursing leadership, CNL, care coordination, innovation, interdependency